Concepts of Database Management, 10th Edition - Lisa Friedrichsen; Lisa Ruffolo; Ellen Monk; Joy L. Starks; Philip J. Pratt (Cengage Learning, 2020)
Strengthen your understanding of database management today with the hands-on, thorough presentation found in CONCEPTS OF DATABASE MANAGEMENT, 10th Edition. Real cases, practical examples and helpful screenshots with concise explanations clarify database design, data integrity, normalization, concurrent updates, data security and big data. Completely updated content reflects Microsoft Access 2019, Office 365 standards and SQL Server 2019, while exploring SQL in a database-neutral environment. Detailed coverage presents the relational model (including QBE and SQL), normalization and views as well as database administration and management. You also examine advanced topics, such as distributed databases, data warehouses, stored procedures, triggers, data macros and Web Apps. Trust this contemporary introduction to help you master today's database techniques to advance your career in any field. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.